Peran Badan Permusyawaratan Desa dalam Meningkatkan Partisipasi Politik Masyarakat Menjelang Pemilu 2024 - Putriawati; Adrian; Marliana, Rina (Mores: Jurnal Pendidikan Hukum, Politik, dan Kewarganegaraan, 2025)
This research was motivated by the lack of community political participation in Margahurip village. The method used in this research is a descriptive method with a qualitative approach and data collection techniques through observation, interviews and documentation. Based on the research results, it shows that the Village Consultative Body (BPD) as a legislative institution at the village level plays an active role in socializing the importance of political participation to the community by holding various activities, such as citizen forums, open discussions and seminars, to increase community political awareness. The obstacles faced by the Village Consultative Body (BPD) in increasing community political participation ahead of the 2024 general election in Margahurip village are differences in educational and economic backgrounds, political apathy, lack of access to information, BPD's internal constraints, unsupportive government policies, and money practices. politics and difficulty determining the right time for socialization. The solution implemented by the Village Consultative Body (BPD) to overcome obstacles in increasing community political participation ahead of the 2024 general election in Margahurip village includes direct outreach in crowded places, the use of digital technology, and increasing communitybased activities. BPD also seeks to educate the public about the negative impacts of money politics and strengthen its supervisory function. Collaboration with other institutions is also a focus for BPD in overcoming obstacles to political participation.